2016
DOI: 10.3389/fvets.2016.00037
|View full text |Cite
|
Sign up to set email alerts
|

Lameness Affects Cow Feeding But Not Rumination Behavior as Characterized from Sensor Data

Abstract: Using automatic sensor data, this is the first study to characterize individual cow feeding and rumination behavior simultaneously as affected by lameness. A group of mixed-parity, lactating Holstein cows were loose-housed with free access to 24 cubicles and 12 automatic feed stations. Cows were milked three times/day. Fresh feed was delivered once daily. During 24 days with effectively 22 days of data, 13,908 feed station visits and 7,697 rumination events obtained from neck-mounted accelerometers on 16 cows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 32 publications
3
40
2
Order By: Relevance
“…It has been demonstrated that lame cows present reduced eating times, and less frequent visits to the concentration feeder than normal cows [43]. In addition, it was shown a reduction in food intake and feed frequency in lame cows compared to normal cows [39]. The lower cholesterol concentrations in lame cows can be explained by lower food intake, which is caused by lameness [18,21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that lame cows present reduced eating times, and less frequent visits to the concentration feeder than normal cows [43]. In addition, it was shown a reduction in food intake and feed frequency in lame cows compared to normal cows [39]. The lower cholesterol concentrations in lame cows can be explained by lower food intake, which is caused by lameness [18,21].…”
Section: Discussionmentioning
confidence: 99%
“…Parameters such as step length, step height and back curvature are measured in such systems to detect the degree of impaired locomotion. Also, techniques involving the attachment of accelerometers to the limbs to measure the accelerations during locomotion [42] and sensitive walkways containing pressure sensors [43] are related to kinematic principle.…”
Section: Automated Lameness Detection Methodsmentioning
confidence: 99%
“…Cows affected with lameness experience hyperalgesia (increased sensitivity to pain), which can persist for ≥28 d (Whay et al, 1998;Whay et al, 2005). Pain associated with lameness can alter feeding behavior in affected cows (Thorup et al, 2016), decrease feed intake (Shonka and Spurlock, 2014), a subsequent decrease in body condition (Gráff et al, 2016), and a prolonged state of negative energy balance that can affect follicular growth, oocyte quality, and embryo survival (Santos and Ribeiro, 2014). Another explanation is that lameness can stimulate a systemic inflammatory response, including an increased gene expression for proinflammatory cytokines (O'Driscoll et al, 2015), which can affect follicular growth and oocyte quality.…”
Section: Pregnancy Loss As a Function Of Exposure To Mastitis During mentioning
confidence: 99%